Pulmonary tuberculosis after therapy with anti-tumor necrosis factor (Tnf) for crohn disease: A case report - da Silva, Douglas Inomata Cardoso [UNESP]; Santos, Bruna Helena de Oliveira [UNESP]; Renosto, Fernanda Lofiego [UNESP]; Watanabe, Erika Mayumi [UNESP]; Herrerias, Giédre Soares Prates [UNESP]; Saad-Hossne, Rogerio [UNESP]; Baima, Julio Pinheiro [UNESP]; Sassaki, Ligia Yukie [UNESP] (My University, 2021)
Background: Challenging differential diagnosis Adalimumab is a biological anti-tumor necrosis factor (TNF) agent which induces and maintains remission in patients with moderate-to-severe Crohn disease (CD). An adverse effect of its use is reactivation of latent in-fections, such as tuberculosis (TB). TB is caused by Mycobacterium tuberculosis and continues to be an impor-tant public health problem in some developing countries, such as Brazil. The present report describes the case of a patient with CD who developed pulmonary TB while receiving adalimumab therapy. A 38-year-old penitentiary worker presented with colonic CD that was intolerant to azathioprine and was started on adalimumab. After 3 months, he experienced coughing, fever, and weight loss, and was diagnosed with pulmonary TB. A chest X-ray and tuberculin skin test performed before he started taking adalimumab were negative for latent TB. The patient was treated for 9 months to cure his infection. The use of adalimumab was suspended while the TB was investigated and he took mesalazine to achieve clinical and endoscopic remission of CD. Adequate screening and chemoprophylaxis for latent TB are indicated in patients at high risk of infection. In patients with inflammatory bowel disease, after anti-TNF therapy is started, strict monitoring is required so that opportunistic infections can be detected early and morbidity and mortality reduced in this population.
Keywords: Adalimumab; Crohn Disease; Inflammatory Bowel Diseases; Latent Tuberculosis